Calculations of the active mode and energetic barrier to electron attachment to CF3 and comparison with kinetic modeling of experimental results. Issue 45 (3rd November 2016) - Han, Huixian; Alday, Benjamin; Shuman, Nicholas S.; Wiens, Justin P.; Troe, Jürgen; Viggiano, Albert A.; Guo, Hua
Abstract : Six-dimensional potential energy surfaces of both CF3 and CF3 − were developed by fitting ∼3000 ab initio points using the permutation invariant polynomial-neural network (PIP-NN) approach. Abstract : To provide a deeper understanding of the kinetics of electron attachment to CF3, the six-dimensional potential energy surfaces of both CF3 and CF3 − were developed by fitting ∼3000 ab initio points per surface at the AE-CCSD(T)-F12a/AVTZ level using the permutation invariant polynomial-neural network (PIP-NN) approach. The fitted potential energy surfaces for CF3 and CF3 − had root mean square fitting errors relative to the ab initio calculations of 1.2 and 1.8 cm −1, respectively. The main active mode for the crossing between the two potential energy surfaces was identified as the umbrella bending mode of CF3 in C 3v symmetry. The lowest energy crossing point is located at R CF = 1.306 Å and θ FCF = 113.6° with the energy of 0.051 eV above the minimum of the CF3 electronic surface. This value is only slightly larger than the experimental data 0.026 ± 0.01 eV determined by kinetic modeling of electron attachment to CF3 . The small discrepancy between the theoretical and experimentally measured values is analyzed.